Log canonical thresholds of quasi-ordinary hypersurface singularities - Budur, Nero; González Pérez, Pedro Daniel; González Villa, Manuel (Proceedings of the American Mathematical Society, 2012)
The log canonical thresholds of irreducible quasi-ordinary hypersurface singularities are computed using an explicit list of pole candidates for the motivic zeta function found by the last two authors.
Gesehen am 13.07.2018